2013
DOI: 10.33064/25lm2013866
|View full text |Cite
|
Sign up to set email alerts
|

Pacientes referidos al Centro Estatal de Vasectomías, factores para la aceptación o rechazo del método

Abstract: Objetivo: Identificar los factores socio-culturales que intervienen en la aceptación y el rechazo de vasectomía en hombres que utilizan los servicios de salud de un medio urbano en la ciudad de Aguascalientes. Metodología: Se realizó un estudio observacional, transversal, descriptivo y comparativo, incluyendo 48 hombres que aceptaron realizarse la vasectomía y 48 que la rechazaron, muestreados aleatoriamente del Centro Estatal de Vasectomía de la Secretaría de Salud. Se midieron variables socio-culturales, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was surprising that the SNN of neither group of participants contained any word that implied decrease of virility or decrease of sexual function. It is possible that the fear that vasectomy affects the sexual function is hidden in other answers, as has already been suggested (García-Franco, Hernández-Flores, & Góngora-Ortega, 2013). Answers that may hide this fear include “I would react with .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It was surprising that the SNN of neither group of participants contained any word that implied decrease of virility or decrease of sexual function. It is possible that the fear that vasectomy affects the sexual function is hidden in other answers, as has already been suggested (García-Franco, Hernández-Flores, & Góngora-Ortega, 2013). Answers that may hide this fear include “I would react with .…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study, it was reported that although men with higher education had received better preparation regarding sexual health issues than less educated men, some of them did not react positively when they were asked if they were willing to undergo a vasectomy (Vega-Briones & Jaramillo-Cardona, 2010). García-Franco et al (2013) reported that although there is a relationship between knowledge about vasectomy and its acceptance, there are men who, despite being informed and having health personnel suggest a vasectomy, reject the procedure because they continue thinking it would negatively affect their sexual potency. It is indispensable to acknowledge that the suggestion of a vasectomy implies something more than a recommendation for family planning, since vasectomy may run counter to some previously acquired values and, for many men, the idea of a vasectomy throws into question the meaning of a culturally learned masculinity (Córdoba-Basulto & Sapién, 2013).…”
Section: Discussionmentioning
confidence: 99%